A historical review of educational dualism in the muslim classical era - Rahimah, Embong; Fadzli, Adam; Anis, Abdullah (2015)
This paper reviews the evolution of Islamic education system and examines the symptoms of dualism in the classical era of Muslim history. The first part of this paper provides a chronological picture of the developments of Islamic education including its institutions and curriculum in the classical era. There are four phases are identified in the Islamic educational development. The first is the phase of its construction and establishment from the period of the Prophet (P.B.U.H) (632 A.D.) to the end of the Umayyad dynasty (749 A.D./41-132 A.H.). The second is the phase of flourishing period during the Abbasid caliphate in the East until the Tartar invasion in 1258A.D/659A.H. The third is the phase of decline and stagnation during the Ottoman period. The final is the phase of revitalization and educational reform from the end of Ottoman Empire until to the present day. The focus of discussion is only the first three phases which are classified under the classical era of Islamic education i.e. 622- 1300A.D. (1-700A.H.). The second part of this paper analyzes whether there existed any symptoms of dualism at the beginning of Muslim history. Dualism is identified as the major contributing factor for the Ummatic malaise. It is found that notwithstanding, the nature of present dualism is quite different, its symptoms had been recognized in the earlier Muslim history such as the emergence of traditionalism and rationalism and the dichotomy between politics and religion. On the other hand, the art of integration had been practiced among Muslim intelligentsias at their individual level and they emphasized the role of the Holy Qur’an and promoted Islamic Intellectualism. This study gives some implications on Muslim life and civilization including the system of education and its learning institutions.